Urgencias médico odontológicas en pacientes pediátricos - López Velarde, Diego Ariel (2023)
ABSTRACT The medical emergencies that can occur during dental care play a fundamental role due to the fact that both the health professional and the child life commitment are involved. The objective of this study was to analyze the medical-dental emergencies in pediatric patients by means of a bibliographic review, the method used in the following research is descriptive, bibliographic, based on a review of articles indexed in Scopus and Latindex published in the last five years of free access, allowing us to obtain updated and truthful information, These articles were mainly obtained from the Pubmed search engine where a total of 29 articles were determined as a total potential sample for the development of the study. The results obtained through the research indicate that in pediatric patients who are in dental care situations, medical and dental emergencies can arise, such as allergic reactions, anaphylaxis, myocardial infarction or hypoglycemia. In pediatric health, emergencies may be linked to specific diseases, whereas, in the dental setting, they are more related to reactions to medications or procedures. Although there are similar symptoms, such as respiratory difficulty and pallor, there are also differences, such as the possibility of aspiration of foreign bodies in the dental office. This information obtained allows us to conclude that it is vitally important for medical and dental personnel to be prepared to deal with these situations, prioritizing patient safety, and that it is important to remain calm during a medical emergency, which will allow us to make a correct diagnosis and thus determine the plan of care during a dental medical emergency. Key words: Dental Medical Emergencies, Pediatric Dentistry, Children, Risk of life.